1982
DOI: 10.1007/bf00441298
|View full text |Cite
|
Sign up to set email alerts
|

Square-Wave Endurance Exercise Test (SWEET) for training and assessment in trained and untrained subjects

Abstract: In order to obtain information about physiological and homeostasic responses at the maximal Intensity of Endurance of the 45 min "Square-Wave Endurance Exercise Test" (MIE45), three arterial blood samples were taken: (a) at rest; (b) at the 45th min of the SWEET; (c) after 15 min of recovery, to measure paO2, paCO2, [H+], [Hb], and [lactate] in 14 normal male subjects: four trained (T) six well trained (WT) and four others untrained (U). Total mechanical work (TMW) corresponding to MIE45 was significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 14 publications
3
41
0
Order By: Relevance
“…The present endurance-training program allowed a significant improvement (p < 0.001) of V . O 2 peak and POpeak, as previously found in the literature (Gimenez et al, 1982;Horowitz et al, 1994;Nickleberry and Brooks, 1996). The increase of V .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present endurance-training program allowed a significant improvement (p < 0.001) of V . O 2 peak and POpeak, as previously found in the literature (Gimenez et al, 1982;Horowitz et al, 1994;Nickleberry and Brooks, 1996). The increase of V .…”
Section: Discussionsupporting
confidence: 85%
“…Endurance training improves physical work capacity and the specific skills of exercise performance, depending on which training program is used (Jones and Carter, 2000). For example, Gimenez et al (1982) showed that specific leg training with the Square-Wave Endurance Exercise Test (SWEET) significantly increased endurance capacity in healthy subjects. Both physiological and pedaling skill adaptations are usually observed after cycling training (Jones and Carter, 2000;Takaishi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Given the lack of recommendations for exercise during adjuvant breast cancer treatments (particularly regarding type, duration, or frequency), we propose a specific endurance training in our training group called the Square-Wave Endurance Exercise Test (SWEET) validated by Gimenez et al [50]. This bi-level training aims to replicate interval training sessions (moderate and high intensity) adjusted according to the physical characteristics of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This bi-level training aims to replicate interval training sessions (moderate and high intensity) adjusted according to the physical characteristics of the subjects. It has previously been proposed with healthy subjects [50], but also with patients suffering from cardiovascular [51, 52] or other diseases [53, 54]. SWEET is quite efficient in increasing maximal oxygen consumption, endurance capacity, and/or force and endurance of the leg muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Interval training has been performed with efficiency in heart transplant recipients in our laboratory (10,(17)(18)(19). The "tailored" 6-wk endurance training program, derived from the square wave endurance exercise test of Gimenez et al (12) led to significant improvements, with an increase of aerobic work capacity (19), lactate removal (18), and changes in muscular ultrastructural characteristics that were similar to age-matched controls under the same relative intensity training (17). Such exercise rehabilitation is also proposed to patients with chronic obstructive pulmonary disease (COPD) (11).…”
mentioning
confidence: 99%